Insulating glazing with improved residual load resistance
By optimizing the waviness-to-thickness ratio and using a polymer interlayer with a melting temperature up to 220°C, the double glazing system enhances residual load resistance and shear strength, addressing safety concerns in overhead applications.
Patent Information
- Application Number
- JP2024520071
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-21
- Filing Date
- 2022-12-20
- Publication Date
- 2024-12-19
AI Technical Summary
Existing double glazing systems exhibit limited residual load capacity, leading to sagging or delamination under their own weight, posing safety risks, especially in overhead applications.
The double glazing system comprises two glass or glass-ceramic plates bonded with an interlayer material having a waviness-to-thickness ratio of at most 1.0% per mm, a polymer with a melting temperature up to 220°C, and optimized plate positioning to minimize gaps, enhancing adhesion and shear strength.
The solution significantly improves the residual load resistance and shear strength of the glazing, reducing the likelihood of delamination and ensuring safety, particularly in overhead installations.
Smart Images

Figure 2024546223000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to insulating glass with improved residual load resistance. The insulating glass comprises at least two panes of glass or glass ceramics which are bonded to one another by an interlayer. The insulating glass can in particular be used as overhead glazing. The insulating glass is particularly suitable for use as safety glass and / or fire protection glass. [Background technology]
[0002] Insulating glass is known from the prior art. They are usually laminates made of at least two glass or glass-ceramic sheets, which are bonded to one another via a plastic interlayer. A disadvantage of known insulating glass is that they only have a limited residual load-bearing capacity. If breakage occurs in one or more sheets of such insulating glass, in particular in a laminate, it often cannot support additional weight any more and starts to sag or delaminate under its own weight, which may result in the detachment of the laminate or parts of it from the frame holder. This may lead to serious dangers in some cases, in particular because the sheets usually have a large weight and, moreover, the small fragments may have sharp edges. Furthermore, damage may occur to objects against which the sheets or parts of the sheets collide. The greatest danger in this respect arises from overhead glazing. Summary of the Invention [Problem to be solved by the invention]
[0003] Against this background, the object of the present invention is to overcome the drawbacks of the prior art. In particular, insulating glass should be provided that is outstandingly suitable for overhead glazing and has an improved residual load resistance. This object is achieved by the subject matter of the claims. [Means for solving the problem]
[0004] In one embodiment, the present invention provides an insulating glass comprising at least two panes and an interlayer of an interlayer material between the panes, the interlayer comprising: the ratio of the sum of the waviness of both plates (in mm per 300 mm each) to the thickness (in mm) of the intermediate layer is at most 1.0% per mm; the intermediate layer material comprises at least one polymer and has a melting temperature of up to 220°C; and both plates are, independently of each other, glass or glass-ceramic plates; The present invention relates to insulating glass.
[0005] In one embodiment, the insulating glass consists of both sheets and an interlayer. Optionally, there is exactly one interlayer between the sheets, in particular there is no further layer. It is also possible to provide one or both sheets with an additional coating, in particular on the side opposite to the interlayer. In some embodiments, there may be one or more further sheets.
[0006] In a further aspect, the present invention relates to an insulating glazing comprising at least one first ply and at least one second ply and an interlayer of an interlayer material between both plies, both plates are, independently of each other, glass or glass-ceramic plates, The first plate has a maximum height H at xy coordinates (x1, y1) in the range that specifies the waviness. max1 and the second plate has a maximum height H at xy coordinates (x2, y2) in the range that specifies the waviness. max2 and Both sheets are in the insulating glass at their maximum height above the first sheet (H max1 ) is a gap having a maximum height (H max2 ) relates to said insulating glass which is arranged differently such that with respect to the coordinates |x1-x2| ≧ 5 mm and / or |y1-y2| ≧ 5 mm.
[0007] Insulating glass with insufficient residual load-bearing capacity tends to sag or delaminate under its own weight in the event of breakage, which may result in the laminate or parts of it peeling off from the frame holder. In the case of insulating glass with good residual load-bearing capacity, this tendency is significantly less evident. The residual load-bearing capacity therefore indicates the ability of the insulating glass to still support its own weight after the breakage of the panes. The residual load-bearing capacity of insulating glass is essentially determined by the degree of adhesion between the panes and the plastic interlayer, which is also reflected in a good shear strength. This degree in turn depends on several parameters. The waviness of the panes, the thickness of the interlayer and the melting temperature of the interlayer material are of particular importance.
[0008] The insulating glass according to the invention comprises at least two panes and an interlayer of an interlayer material between the panes, each of the panes having a predetermined waviness.
[0009] Plate waviness is detrimental because significant waviness makes uniform contact between the plate and the interlayer difficult and can lead to poor adhesion. To counteract this effect, the thickness of the interlayer can be increased. However, particularly thick interlayers are usually undesirable, so leveling out plate waviness by increasing the thickness of the interlayer is only advantageous to a certain extent.
[0010] The waviness of each of the two sheets can be determined by placing a measuring body with a flat measuring surface, in particular a ruler with a length of 300 mm, on the side of the sheet facing away from the interlayer, so that the measuring body does not protrude beyond the edge of the sheet. In other words, the waviness can also be determined by measuring not the side of the sheet facing away from the interlayer, but the side facing the interlayer. However, it is more practical to measure the side facing away from the interlayer, since this measurement can be carried out non-destructively on insulating glass.
[0011] The TTV (Total Thickness Variation) of the plate is particularly small compared to the waviness, which can therefore be described as a parameter of the plate itself, without any distinction between both sides of the plate, and can be determined by measurements with measuring bodies representative of each of both sides.
[0012] The TTV is specified as the difference between the maximum thickness and the minimum thickness of the plate. Each plate may have a TTV of, for example, at most 0.4 mm, at most 0.3 mm, or at most 0.2 mm. The quotient of the waviness (mm per 300 mm) and the TTV (mm) may, for example, be in the range of 1.0 to 20.0 per meter, in particular 2.0 to 15.0 per meter, or in the range of 5.0 to 10.0 per meter, for each plate. The quotient of the waviness and the TTV may, for example, be at least 1.0 per meter, 2.0 per meter, or 5.0 per meter. The quotient of the waviness and the TTV may, for example, be at most 20.0 per meter, at most 15.0 per meter, or at most 10.0 per meter.
[0013] To measure the waviness, a measuring body is usually placed on the plate at two or more points, while due to the waviness of the plate, a gap occurs between the measuring body and the plate surface at other positions. The height of such a gap can be determined, for example, by using a feeler gauge, in particular by arranging the feeler gauge between the plate surface and the measuring body and increasing the thickness of the feeler gauge so that the gap between the plate surface and the measuring body is just filled at the position of the maximum distance between the plate surface and the measuring body. The thickness of the feeler gauge then corresponds to the height of the gap. Depending on the position at which the measuring body is placed on the plate surface, gaps of different heights can occur. The gap with the highest height of all gaps is relevant for determining the waviness. This height is determined by H max It is also called the waviness and is expressed in mm. max It is expressed as the quotient of the length of the measurement body (mm) and 300 mm. The waviness can be stated as a percentage description by abbreviating the unit mm. max If is for example 3 mm, then the waviness is obtained as the quotient of 3 mm and 300 mm, and is therefore 1.0%.
[0014] The waviness of both sheets of insulating glass is not necessarily the same. In practice, both sheets often have different waviness. The sum of the waviness of both sheets is of practical importance, since it is this that determines the degree of change in the gap between the sheets. This sum should be as small as possible. The disadvantage of a large sum of waviness can be countered to some extent by a relatively large interlayer thickness, as mentioned above.
[0015] However, the ratio of the sum of the waviness of both plates (in mm per 300 mm each) to the thickness of the intermediate layer (in mm) should not exceed a value of 1.0% per mm. In particularly preferred embodiments, the ratio of the sum of the waviness of both plates to the thickness of the intermediate layer is at most 0.9% per mm, at most 0.8% per mm, at most 0.7% per mm, at most 0.6% per mm, at most 0.5% per mm or at most 0.4% per mm only.
[0016] When manufacturing the insulating glass, it is also possible to take care that the two sheets are arranged relative to one another in such a way that the crests or troughs of the two sheets are exactly opposite one another, so that no particularly large gaps between the sheets occur. In particular, the sheets are arranged such that the maximum height (H max1 ) and a maximum height (H max2 ) may be arranged so that the gaps having the wavy peaks and the wavy valleys do not directly face each other. Usually, due to manufacturing, the wavy valleys and the wavy peaks are generated at regular intervals. Therefore, when the wavy valleys are prevented from facing each other, the wavy valleys are also prevented from facing each other.
[0017] To describe the position of the gap on the plate, for example, a coordinate system can be defined, where one corner of the plate has xy coordinates (0,0), while the coordinates of the opposite corner of the plate correspond exactly to the length and width of the plate. For a plate having a length of 2000 mm and a width of 1000 mm, the four corners of the plate have, for example, xy coordinates (0 mm, 0 mm), (0 mm, 1000 mm), (2000 mm, 0 mm), and (2000 mm, 1000 mm). In insulating glass, the corresponding positions of both plates each have the same xy coordinates. Thus, a point with coordinates (250 mm, 500 mm) on the first plate lies, for example, exactly opposite a point with coordinates (250 mm, 500 mm) on the second plate.
[0018] The maximum height on the first plate (H max1 The gap has x- and y-coordinates (x1, y1). The maximum height (H max2 ) has xy coordinates (x2, y2). Both sheets of insulating glass preferably have a maximum height (H max1 ) on the second plate, the gap has a maximum height (H max2 ) are arranged differently with respect to the coordinate axes such that |x1-x2|≧5 mm and / or |y1-y2|≧5 mm. Optionally, |x1-x2|≧10 mm and / or |y1-y2|≧10 mm, in particular |x1-x2|≧15 mm and / or |y1-y2|≧15 mm, or |x1-x2|≧20 mm and / or |y1-y2|≧20 mm.
[0019] A further effect that can be used to counteract the waviness problem of the sheet is the flow behavior of the interlayer material. If an interlayer material with good flow properties is used, the waviness of the sheet can be at least partially equalized during the manufacture of the insulating glass by heating the interlayer material to a temperature that allows it to flow or at least spread to the defect locations due to the waviness or to the locations that have little interlayer material. However, arbitrarily high temperatures should not be used for this purpose. Interlayer materials with relatively low melting temperatures have therefore proven advantageous. The melting temperature is preferably in the range of 180-220°C, for example 190-210°C. Unless otherwise indicated, the melting temperatures in this disclosure relate to melting temperatures at standard pressure (101,325 kPa). The melting temperature of the interlayer material is at most 220°C, for example at most 210°C. The melting temperature of the interlayer material can be at least 180°C, or at least 190°C, for example.
[0020] At least one of both plates, preferably each of both plates, may have a thickness in the range of, for example, 2.0 to 15.0 mm, in particular 2.0 to 10.0 mm, 2.5 to 7.5 mm, 3.0 to 6.0 mm, or 3.5 to 5.5 mm. At least one of both plates, in particular each of both plates, may have a thickness of, for example, at least 2.0 mm, at least 2.5 mm, at least 3.0 mm, or at least 3.5 mm. At least one of both plates, in particular each of both plates, may have a thickness of, for example, up to 15.0 mm, up to 10.0 mm, up to 7.5 mm, up to 6.0 mm, or up to 5.5 mm.
[0021] The intermediate layer may have a thickness in the range of, for example, 0.3 to 5.0 mm, in particular 0.4 to 4.0 mm, 0.5 to 3.0 mm, 0.6 to 2.0 mm, or 0.7 to 1.0 mm. The thickness of the intermediate layer may be, for example, at least 0.3 mm, at least 0.4 mm, at least 0.5 mm, at least 0.6 mm, or at least 0.7 mm. The thickness of the intermediate layer may be, for example, up to 5.0 mm, up to 4.0 mm, up to 3.0 mm, up to 2.0 mm, or up to 1.0 mm.
[0022] The insulating glass may have a thickness in the range of, for example, 5.0 to 15.0 mm, in particular in the range of 6.0 to 14.0 mm, 7.0 to 13.0 mm, 8.0 to 12.0 mm or 9.0 to 11.0 mm. The thickness of the insulating glass may be, for example, at least 5.0 mm, at least 6.0 mm, at least 7.0 mm, at least 8.0 mm or at least 9.0 mm. The thickness of the insulating glass may be, for example, up to 15.0 mm, up to 14.0 mm, up to 13.0 mm, up to 12.0 mm or up to 11.0 mm.
[0023] Both plates can be glass plates or glass ceramic plates, independently of each other. In some embodiments, both plates are glass plates, especially borosilicate glass plates. In some embodiments, both plates are glass ceramic plates. In some embodiments, one of both plates is a glass plate, especially a borosilicate glass plate, and the other of both plates is a glass ceramic plate. In some embodiments, at least one of both plates is a glass plate, especially a borosilicate glass plate. In some embodiments, at least one of both plates is a glass ceramic plate. In some embodiments, at most one of both plates is a glass plate, especially a borosilicate glass plate. In some embodiments, at most one of both plates is a glass ceramic plate. In some embodiments, at least one of both plates is a borosilicate glass plate, or a glass ceramic plate. In some embodiments, both plates are a glass ceramic plate, or a borosilicate glass plate.
[0024] The glass panes can in particular be soda-lime or borosilicate glass panes, where glasses having a proportion of B2O3 in the range of 7% to 15% by weight are referred to as borosilicate glasses.
[0025] The glass ceramic plate is a plate made of glass ceramic. The glass plate is a plate made of glass. The soda-lime glass plate is a plate made of soda-lime glass. The borosilicate glass plate is a plate made of borosilicate glass, in particular glass having a proportion of B2O3 in the range of 7% to 15% by weight.
[0026] The intermediate layer material comprises a polymer, which can be, for example, polyurethane (PU).
[0027] In one embodiment of the invention, the insulating glass has fire-resistant properties. With the insulating glass of the invention, a fire resistance rating of at least EW60, more preferably at least EW90, more preferably at least EW120 according to DIN EN 13501-1:2010-01 is preferably achieved.
[0028] With the insulating glazing according to the invention, for example fire resistance ratings according to DIN EN 13501-1:2010-01 of at least E30, at least E60, at least E90, at least E120 or at least E180 can be achieved.
[0029] With the insulating glass according to the invention, for example, a fire resistance rating of at least UL 9, or at least UL 10, especially including the hose stream test, can be achieved. The fire resistance time can be, for example, at least 45 minutes, at least 60 minutes, at least 90 minutes, at least 120 minutes or at least 180 minutes.
[0030] The interlayer material may, for example, include a flame retardant material, or a combination of two or more flame retardant materials, in addition to a polymer.
[0031] The flame retardant material may in particular be selected from the group consisting of bromine-containing compounds (in particular polybrominated diphenyl ethers (PBDEs), brominated alcohols, and / or polybrominated cycloalkanes), phosphate-containing compounds, chlorinated compounds, inorganic flame retardants (in particular aluminum hydroxide), and combinations of two or more thereof. Preferably, the flame retardant material is selected from the group consisting of polybrominated diphenyl ethers (PBDEs), brominated alcohols, polybrominated cycloalkanes, phosphate-containing compounds, and combinations of two or more thereof.
[0032] The polybrominated diphenyl ether can in particular be decabromodiphenyl ether.
[0033] The brominated alcohol may be selected, for example, from the group consisting of dibromoneopentyl alcohol, tribromoneopentyl alcohol, tetrabromobisphenol A (TBBA), dibromobutenediol, and combinations of two or more thereof.
[0034] The polybrominated cycloalkane can be, for example, hexabromocyclodecane (HBCD).
[0035] The phosphate-containing compound may, for example, be selected from the group consisting of tricresyl phosphate, cresyl diphenyl phosphate, dicresyl phenyl phosphate, triphenyl phosphate, and combinations of two or more thereof.
[0036] The flame retardant material may in particular be selected from the group consisting of tricresyl phosphate, cresyl diphenyl phosphate, dicresyl phenyl phosphate, triphenyl phosphate, and combinations of two or more thereof.
[0037] The flame retardant material may in particular be selected from the group consisting of dibromoneopentyl alcohol, tribromoneopentyl alcohol, tetrabromobisphenol A (TBBA), dibromobutenediol, and combinations of two or more thereof.
[0038] The flame retardant material may in particular be selected from the group consisting of tricresyl phosphate, cresyl diphenyl phosphate, dicresyl phenyl phosphate, triphenyl phosphate, dibromoneopentyl alcohol, tribromoneopentyl alcohol, tetrabromobisphenol A (TBBA), dibromobutenediol, and combinations of two or more thereof.
[0039] A disadvantage of insulating glass according to the prior art is that it tends to swell strongly in the event of a fire. This can be at least partly attributed to the significant volume expansion of the interlayer material, especially at relatively low temperatures. This so-called degassing of the interlayer material can lead to a large pressure increase in the insulating glass, which can then be associated with the occurrence of bulging of the insulating glass and destruction of the panes.
[0040] To counteract such a drawback, the interlayer material can be advantageously selected to have a relatively high proportion of inorganic substances that cannot form air pressure. Alternatively or additionally, it may be advantageous if the decomposition of the interlayer material proceeds slowly, especially at relatively low temperatures. If the pressure buildup proceeds slowly, the possibility of pressure reduction through the edge regions of the insulating glass that were previously open is improved. However, at somewhat higher temperatures, a faster decomposition is advantageous. This makes it possible to avoid further decomposition phenomena that are too pronounced at particularly high temperatures, since at these particularly high temperatures a large part of the interlayer material has already decomposed and is therefore no longer available for further decomposition phenomena. Otherwise, during the later decomposition, gases escaping on the non-fire side may ignite due to the already too high temperatures.
[0041] The intermediate layer material is particularly suitable if the intermediate material has one or more of the following properties: A relatively high proportion of inorganic matter that cannot form atmospheric pressure; slow decomposition at low temperatures (especially in the range of 100°C to 200°C); Rapid decomposition at moderate temperatures (especially in the range of 275°C to 425°C) may be selected to have
[0042] A relatively high proportion of inorganic substances that cannot form atmospheric pressure is present if the intermediate layer material is selected such that it has a high ignition residue. The ignition residue can be determined in accordance with DIN EN ISO 3451-1:2019-05 (Plastics - Determination of ash - Part 1: General methods). To determine the ignition residue, the intermediate material is heated, in particular to a temperature of 625°C, in order to burn off the organic compounds and leave only the inorganic part (the so-called ignition residue). The ignition residue is usually indicated as a mass percentage based on the total mass of the material investigated. The ignition residue of the intermediate layer material (at a temperature of 625°C) in accordance with DIN EN ISO 3451-1:2019-05 can be, for example, at least 0.20% by weight, at least 0.25% by weight, or at least 0.30% by weight. These lower limits characterize the previously mentioned large ignition residue. The ignition residue of the intermediate layer material according to DIN EN ISO 3451-1:2019-05 (at a temperature of 625°C) can be, for example, at most 0.75% by weight, at most 0.50% by weight, or at most 0.40% by weight. The ignition residue of the intermediate layer material according to DIN EN ISO 3451-1:2019-05 (at a temperature of 625°C) can be, for example, in the range of 0.20 to 0.75% by weight, 0.25 to 0.50% by weight, or 0.30 to 0.40% by weight.
[0043] Dynamic differential scanning calorimetry (in English "differential scanning calorimetry (DSC)"), also called differential thermal analysis, is a method by which the heat released or absorbed by an interlayer material when this material is heated can be measured. This method is particularly suitable for determining the degree of decomposition of materials at low temperatures. The method can in particular be carried out in accordance with DIN EN ISO 11357-1:2017-02 (Plastics - Dynamic Differential Thermal Analysis (DSC)). In particular, so-called power compensating differential scanning calorimetry (in English "power compensating DSC") can be used. In this case, a sample of the interlayer material and a reference vessel are placed in a thermally isolated oven, which is controlled so that the same temperature always prevails on both sides. The power required for this can be determined as a function of the temperature. The interlayer material can in particular be selected such that the power required in the power-compensating differential scanning calorimetry is on average at most 0.60 mW per mg of interlayer material in the temperature range from 100°C to 200°C. The required power can be, for example, less than 0.60 mW / mg, in particular up to 0.55 mW / mg. The required power can be, for example, at least 0.40 mW / mg, in particular above 0.40 mW / mg, or at least 0.45 mW / mg. The required power can be, for example, in the range of 0.40-0.60 mW / mg, >0.40-<0.60 mW / mg, or 0.45-0.55 mW / mg.
[0044] A method that allows decomposition at high temperatures to be determined particularly well is the so-called thermogravimetric analysis (TGA), also referred to as thermogravimetry. In contrast to DSC, in the case of TGA, the change in mass is not determined, but rather the change in heat. In the case of TGA, the sample is subjected to a defined heating program. The mass loss occurring as a function of temperature is measured and the thermal decomposition is characterized. TGA can be carried out in accordance with DIN EN ISO 11358-1:2014-10. In particular, the heating of the sample from 25°C to 600°C is carried out under nitrogen (30 ml N2 / min) with a heating rate of 20 K / min. The interlayer material can be selected, for example, such that 50% by weight of the mass loss of the interlayer material in TGA occurs at a temperature below 425°C, in particular below 420°C, below 410°C, below 400°C, below 390°C or below 380°C. The 50% by weight mass loss of the interlayer material in TGA can occur, for example, at temperatures above 325° C., above 330° C., above 340° C., above 350° C., above 360° C., or above 370° C. The 50% by weight mass loss of the interlayer material in TGA can occur, for example, at temperatures in the ranges of 325-425° C., 330-420° C., 340-410° C., 350-400° C., 360-390° C., or 370-380° C. The limits given for mass loss characterize slow decomposition at the aforementioned low temperatures or fast decomposition at the aforementioned moderate temperatures.
[0045] The intermediate layer material is, for example, 1.00 to 1.25 g / cm 3 , 1.01~1.15g / cm 3 , 1.02~1.10g / cm 3 , or 1.03 to 1.05 g / cm 3 The density of the intermediate layer material can be, for example, at least 1.00 g / cm 3 , at least 1.01 g / cm 3 , at least 1.02 g / cm 3 , or at least 1.03 g / cm 3 The density can be, for example, up to 1.25 g / cm 3 , max 1.20g / cm 3 , max 1.15g / cm 3 , max 1.10g / cm 3 , maximum 1.09g / cm3 , maximum 1.08g / cm 3 , maximum 1.07g / cm 3 , maximum 1.06g / cm 3 , or up to 1.05 g / cm 3 A low density is advantageous for lightweight composite glass. The density of the interlayer material can be specified according to ASTM D792, in particular according to ASTM D792:2020.
[0046] The intermediate layer material may have a Shore hardness (Shore A) in the range of, for example, 50 to 95, 60 to 90, 65 to 85, or 70 to 80. The Shore hardness (Shore A) can be, for example, at least 50, at least 60, at least 65, or at least 70. The Shore hardness (Shore A) can be, for example, up to 95, up to 90, up to 85, or up to 80. The Shore hardness may be specified according to ASTM D2240-00.
[0047] The interlayer material may have a stress at 100% extension in the range of, for example, 5.0 to 15.0 MPa, 6.0 to 14.0 MPa, 7.0 to 13.0 MPa, or 8.0 to 12.0 MPa. The stress at 100% extension may be, for example, at least 5.0 MPa, at least 6.0 MPa, at least 7.0 MPa, or at least 8.0 MPa. The stress at 100% extension may be, for example, up to 15.0 MPa, up to 14.0 MPa, up to 13.0 MPa, or up to 12.0 MPa. The stress at 100% extension may be specified according to ASTM D412, in particular according to ASTM D412-16 (2021).
[0048] The interlayer material may have a stress at 300% elongation in the range of, for example, 10.0 to 25.0 MPa, 11.0 to 24.0 MPa, 12.0 to 23.0 MPa, 13.0 to 22.0 MPa, 14.0 to 21.0 MPa, or 15.0 to 20.0 MPa. The stress at 300% elongation may be, for example, at least 10.0 MPa, at least 11.0 MPa, at least 12.0 MPa, at least 13.0 MPa, at least 14.0 MPa, or at least 15.0 MPa. The stress at 300% elongation may be, for example, up to 25.0 MPa, up to 24.0 MPa, up to 23.0 MPa, up to 22.0 MPa, up to 21.0 MPa, or up to 20.0 MPa. The stress at 300% elongation may be specified according to ASTM D412, in particular according to ASTM D412-16 (2021).
[0049] The tensile strength of the intermediate layer material can be, for example, in the range of 5.0 to 50.0 MPa, 10.0 to 40.0 MPa, 15.0 to 30.0 MPa, or 17.0 to 25.0 MPa. The tensile strength of the intermediate layer material can be, for example, at least 5.0 MPa, at least 10.0 MPa, at least 15.0 MPa, or at least 17.0 MPa. The tensile strength of the intermediate layer material can be, for example, up to 50.0 MPa, up to 40.0 MPa, up to 30.0 MPa, or up to 25.0 MPa. The tensile strength can be specified in accordance with ASTM D412, in particular in accordance with ASTM D412-16 (2021).
[0050] The intermediate layer material may have a modulus of elasticity up to 10% elongation, for example, in the range of 10.0 to 30.0 MPa, 12.5 to 27.5 MPa, 15.0 to 25.0 MPa, or 16.5 to 21.5 MPa. The intermediate layer material may have a modulus of elasticity up to 10% elongation, for example, of at least 10.0 MPa, at least 12.5 MPa, at least 15.0 MPa, or at least 16.5 MPa. The intermediate layer material may have a modulus of elasticity up to 10% elongation, for example, of up to 30.0 MPa, up to 27.5 MPa, up to 25.0 MPa, or up to 21.5 MPa. The modulus of elasticity up to 10% elongation may be specified according to ASTM D412, in particular according to ASTM D412-16(2021).
[0051] The intermediate layer material may have an average elongation in the range of, for example, 150% to 500%, 200% to 450%, 250% to 400%, or 300% to 350%. The intermediate layer material may have an average elongation of, for example, at least 150%, at least 200%, at least 250%, or at least 300%. The intermediate layer material may have an average elongation of, for example, up to 500%, up to 450%, up to 400%, or up to 350%. The average elongation may be specified according to ASTM D412, in particular according to ASTM D412-16(2021).
[0052] The interlayer material may have a force at break in the range of, for example, 50-200 N, 60-150 N, or 75-100 N. The interlayer material may have a force at break of, for example, at least 50 N, at least 60 N, or at least 75 N. The interlayer material may have a force at break of, for example, up to 200 N, up to 150 N, or up to 100 N. The force at break may be specified according to ASTM D412, in particular according to ASTM D412-16(2021).
[0053] The intermediate layer material may have a tear strength in the range of, for example, 30-200 kN / m, 50-150 kN / m, or 70-100 kN / m. The intermediate layer material may have a tear strength of, for example, at least 30 kN / m, at least 50 kN / m, or at least 70 kN / m. The intermediate layer material may have a tear strength of, for example, up to 200 kN / m, up to 150 kN / m, or up to 100 kN / m. The tear strength may be specified according to ASTM D624, in particular according to ASTM D624-00(2020).
[0054] In one embodiment of the invention, the insulating glass has a flame retardancy according to UL9, 8th edition, March 2020, or according to UL10, in particular UL10B, 10th edition, February 2008, or UL10C, 3rd edition, June 2016, after 90 minutes, preferably after 120 minutes or 180 minutes.
[0055] In one embodiment of the present invention, the insulating glass has good mechanical resistance to external influences. This can be tested, for example, in a pendulum impact test according to the standard ANSI Z97.1-2015 (R2020). The hole in the insulating glass according to the present invention caused by the pendulum impact test with a test specimen having a weight of 45 kg and a drop height of 1220 mm according to ANSI Z97.1-2015 (R2020) can be particularly small so that a ball having a diameter of 76 mm cannot pass through when a force of up to 72 N, up to 36 N, up to 27 N, up to 18 N, up to 12 N or up to 9 N is applied. In one embodiment of the present invention, the insulating glass passes the pendulum impact test according to ANSI Z97.1-2015 (R2020), especially according to the highest classification of this standard.
[0056] In one embodiment of the invention, the insulating glass has a high shear strength. The shear behavior can be determined using the measurement configuration shown in FIG. 1. The measurement setup comprises an upper and a lower holding device, into which the sample to be tested is loaded. The length of the lower holding device is selected in such a way that the sample is supported up to just before the shear end (laminated layer) (FIG. 1). The upper holding device also ends just before the shear end, so that the laminate is exposed during shearing. The support angle is 45°. The force is introduced vertically from above and is divided equally into two force components, one perpendicular to the shear plane and one in the shear direction. The shearing is therefore carried out under load. The travel speed is 2 mm / s. The initial load is 10 N. As test equipment, a tensile compression machine can be used, in particular a universal tensile compression machine, for example the universal tensile compression machine Instron 5969. The measurements are carried out in particular at a temperature of 22° C. and a relative humidity of 40% to 60%, in particular 50%.
[0057] The shear force is measured. The maximum shear force per area can be calculated, for example, by plotting the force on a force vs. path curve over a lateral displacement (Traversenweg) (Figures 2 and 3) and dividing the maximum force read from the curve by the area of the specimen. For example, for a specimen having a length of 20 mm and a width of 10 mm, the specimen area is 20 × 10 mm. 2 =200mm 2 It is.
[0058] The maximum shear force per area is preferably at least 17.5 N / mm for the insulating glass according to the invention. 2 , e.g. at least 18.0N / mm 2 , at least 18.5N / mm 2 , at least 19.0N / mm 2 , at least 19.5N / mm 2 , at least 20.0N / mm 2 , at least 20.5N / mm 2 , at least 21.0N / mm 2 , at least 21.5N / mm 2 , at least 22.0N / mm 2 , at least 22.5N / mm 2 , at least 23.0N / mm2 , at least 23.5N / mm 2 , or at least 24.0N / mm 2 In some embodiments, the maximum shear force per area is up to 50.0 N / mm 2 , max 45.0N / mm 2 , max 40.0N / mm 2 , max 35.0N / mm 2 , max 30.0N / mm 2 , max 29.0N / mm 2 , max 28.0N / mm 2 , or up to 27.5N / mm 2 The maximum shear force per area is, for example, 17.5 to 50.0 N / mm 2 , 18.0~50.0N / mm 2 , 18.5~45.0N / mm 2 , 19.0~40.0N / mm 2 , 19.5~40.0N / mm 2 , 20.0~35.0N / mm 2 , 20.5~35.0N / mm 2 , 21.0~30.0N / mm 2 , 21.5~30.0N / mm 2 , 22.0~29.0N / mm 2 , 22.5~29.0N / mm 2 , 23.0~28.0N / mm 2 , 23.5~27.5N / mm 2 , or 24.0~27.5N / mm 2 The range can be:
[0059] The glass sheets can be, for example, thermally or chemically strengthened, and in particular have a surface compressive stress of at least 50 MPa on the side facing the interlayer and / or on the surface opposite the interlayer. In one embodiment, at least one of both sheets, in particular both sheets, is thermally strengthened. In one embodiment, at least one of both sheets, in particular both sheets, is chemically strengthened. In one embodiment, one of both sheets is chemically strengthened and one of both sheets is thermally strengthened. In one embodiment, neither of both sheets is chemically strengthened. In one embodiment, neither of both sheets is thermally strengthened. In one embodiment, each of both sheets is neither chemically nor thermally strengthened.
[0060] In one embodiment, for example, at least one of both sheets may have at least one fire-polished surface. In one embodiment, both sheets have at least one fire-polished surface. In one embodiment, both sheets each have exactly one fire-polished surface. In double glazing, it is preferred that the sheets are arranged such that the fire-polished surfaces of both sheets each face outward, while the non-fire-polished surfaces of both sheets each face the interlayer. In one implementation, both sheets have two fire-polished surfaces. In one embodiment, one of both sheets has one fire-polished surface, and the other of both sheets has two fire-polished surfaces. In one embodiment, one of both sheets has one fire-polished surface, and the other of both sheets has a non-fire-polished surface. In one embodiment, none of both sheets has a fire-polished surface.
[0061] Flame-polished surfaces are characterized by a particularly low surface roughness. The roughness of a flame-polished surface is smaller than that of a mechanically polished surface. The flame-polished surface or surfaces advantageously have a squared roughness (R q or RMS). tis advantageously at most 6 nm, more preferably at most 4 nm and particularly preferably at most 2 nm. The roughness depth is specified in accordance with DIN EN ISO 4287.
[0062] In one embodiment, for example, at least one of both plates, especially both plates, may have good hydrolytic and / or chemical resistance. The acid resistance of at least one of both plates, especially both plates, according to DIN 12116:2001-03 may, for example, be up to 2.0 mg / dm2 of corrosion in acid. 2 , up to 1.5mg / dm 2 , or up to 1.2 mg / dm 2 The acid resistance according to DIN 12116:2001-03 of at least one of both plates, in particular of both plates, can for example be such that the plate(s) have an acid resistance class of at least 2. The alkali resistance according to DIN ISO 695:1994-02 of at least one of both plates, in particular of both plates, can for example be such that the corrosion in alkaline solutions is at most 100 mg / dm 2 , up to 90mg / dm 2 , up to 80mg / dm 2 , or up to 75 mg / dm 2 The alkali resistance according to ISO 695:1994-02 of at least one of both plates, in particular both plates, can be such that the plate(s) have at least an alkali resistance grade A1. The hydrolysis resistance according to ISO 719:2020-09 of at least one of both plates, in particular both plates, can be such that the corrosion (in glass particles) in water is at most 20 μg Na2O per gram, at most 15 μg Na2O per gram, or at most 10 μg Na2O per gram. The hydrolysis resistance according to ISO 719:2020-09 of at least one of both plates, in particular both plates, can be such that the plate(s) have at least an hydrolysis resistance grade HGB1.
[0063] In one embodiment, at least one of both plates, and particularly each of both plates, may have a transmittance of at least 80% for light having a wavelength in the range of 380-750 nm, and particularly for light over the entire wavelength range of 380-750 nm, at a nominal thickness of 4.0 mm.
[0064] In one embodiment, the intermediate layer material can have a transmittance of at least 80%, at least 85%, or at least 90% for light having a wavelength in the range of 380-750 nm, particularly over the entire wavelength range of 380-750 nm, at a nominal thickness of 380 μm.
[0065] The insulating glass may, for example, have a transmittance of at least 60% for light having a wavelength in the range 380 to 750 nm at a nominal thickness of 8.0 mm, and / or may have a transmittance of at least 60% for light over the entire wavelength range of 380 to 750 nm at a nominal thickness of 8.0 mm.
[0066] Haze is an optical parameter for describing scattering behavior and may be specified according to ASTM D1003, in particular according to ASTM D1003:2013. The insulating glass may have a haze in the range of 0.5% to 3.0%, 1.0% to 2.0%, 1.2% to 1.8%, or 1.4% to 1.6% at a nominal thickness of 8.0 mm. In some embodiments, the insulating glass may have a haze of 0.5% or less at a nominal thickness of 8.0 mm, for example in the range of 0.1% to 0.5%, or 0.2% to 0.4%, in particular about 0.3%.
[0067] In one embodiment, the insulating glass may for example have a length in the range of 500 to 3000 mm and / or a width in the range of 500 to 2000 mm.
[0068] The invention also relates to components, in particular overhead glazing, which comprise insulating glazing according to the invention.
[0069] The invention also relates to the use of insulating glazing according to the invention in components, in particular in overhead glazing.
[0070] The invention also relates to a method for producing insulating glazing, said method in particular comprising the following steps: Providing at least two plates, which are independently glass or glass-ceramic plates; providing an intermediate layer sheet; - placing said sheet between both plates to obtain a composite layer; and Autoclave treatment to obtain double glazing may include.
[0071] The autoclaving step may for example include a temperature in the range of 80° C. to 200° C., e.g. 100° C. to 175° C., 110° C. to 150° C., 120° C. to 140° C., especially 125° C. to 130° C., especially for a time of at least 4 hours and / or up to 8 hours. The autoclaving step may for example include a temperature of at least 120° C., or at least 125° C., especially for a time of at least 4 hours. The autoclaving step may for example include a temperature of up to 140° C., or up to 130° C., especially for a time of up to 8 hours.
[0072] The duration of the autoclaving step can range, for example, from 5 to 9 hours. The autoclaving step can include a heating step, the duration of which is from the start of the autoclaving step to the time at which the autoclaving temperature is reached. The duration of the heating step can be, for example, from 30 to 120 minutes, in particular from 45 to 90 minutes, or about 60 minutes.
[0073] The method further comprises the steps of: preparing a pre-laminate from the composite layers prior to autoclaving; may include.
[0074] The production of the prelaminate can in particular take place with the aid of rollers and / or a vacuum.
[0075] The prelaminate production step may for example involve temperatures in the range of 80°C to 130°C, 90°C to 120°C or 100°C to 110°C, in particular for a time period of 2 to 5 minutes. The prelaminate production step may for example involve temperatures of at least 80°C, at least 90°C or at least 100°C, in particular for a time period of 15 to 120 seconds. The prelaminate production step may for example involve temperatures up to 130°C, up to 120°C or up to 110°C, in particular for a time period of 15 to 120 seconds.
[0076] The duration of the prelaminate production step can range for example from 15 to 120 seconds.
[0077] The autoclave treatment step and / or the preparation step of the pre-laminate may be performed at a pressure of, for example, 100 to 200 g / cm 2 , especially 115~180g / cm 2 , or 130~160g / cm 2 The pressure during the autoclaving step and / or during the preparation of the prelaminate may include, for example, a pressure in the range of at least 100 g / cm 2 , at least 115g / cm 2 , or at least 130g / cm 2 The pressure during the autoclaving step and / or during the preparation of the prelaminate can be, for example, up to 200 g / cm 2 , max 180g / cm 2 , or up to 160g / cm 2 It can be.
[0078] The plate conforming step particularly involves the float process. In order to reduce thickness variations, it is advantageous to keep the drawing speed and / or temperature control as constant as possible. In the case of glass ceramic plates, this also applies to the ceramming step. In particular, a particularly homogeneous temperature control can be achieved by adjusting the bottom, top and side heating circuits.
[0079] Preferred Embodiments In a preferred embodiment, the invention relates to an insulating glazing comprising at least two glass panes, in particular borosilicate glass panes, and an interlayer made of an interlayer material between both panes, the ratio of the sum of the waviness of both plates (in mm per 300 mm each) to the thickness (in mm) of the intermediate layer is at most 1.0% per mm; and the intermediate layer material comprises at least one polymer and has a melting temperature of up to 220°C; The present invention relates to insulating glass.
[0080] In a preferred embodiment, the invention relates to an insulating glazing comprising at least two glass-ceramic panes and an interlayer of an interlayer material between both panes, the ratio of the sum of the waviness of both plates (in mm per 300 mm each) to the thickness (in mm) of the intermediate layer is at most 1.0% per mm; and the intermediate layer material comprises at least one polymer and has a melting temperature of up to 220°C; The present invention relates to insulating glass.
[0081] In a preferred embodiment, the present invention relates to a double glazing having a thickness in the range of 5.0 to 15.0 mm, comprising at least two panes and an interlayer between both panes, the interlayer being made of an interlayer material and having an interlayer thickness in the range of 0.3 to 5.0 mm, the ratio of the sum of the waviness of both plates (in mm per 300 mm each) to the thickness (in mm) of the intermediate layer is at most 1.0% per mm; the intermediate layer material comprises at least one polymer and has a melting temperature of up to 220°C; and both plates are, independently of each other, glass or glass-ceramic plates; The present invention relates to insulating glass.
[0082] In a preferred embodiment, the present invention provides a double glazing comprising at least two glass ceramic panes and an interlayer between both panes made of an interlayer material comprising polyurethane, the interlayer having a strength of at least 17.5 N / mm 2 and a transmittance of at least 60% for light having a wavelength in the range of 380 to 750 nm at a reference thickness of 8.0 mm.
[0083] In a preferred embodiment, the present invention relates to an insulating glazing comprising at least two panes and an interlayer of an interlayer material between both panes, the ratio of the sum of the waviness of both plates (in mm per 300 mm each) to the thickness (in mm) of the intermediate layer is at most 1.0% per mm; the interlayer material comprises at least one polyurethane and additionally one or a combination of two or more flame retardant materials; the intermediate layer material has a melting temperature of up to 220°C; and both plates are, independently of each other, glass or glass-ceramic plates; The present invention relates to insulating glass.
[0084] In a preferred embodiment, the present invention relates to a double-glazing glass having a flame retardant property according to the UL9 standard 8th edition March 2020 after 90 minutes and passing a pendulum impact test according to ANSI Z97.1-2015 (R2020), the insulating glass comprises at least two panes and an interlayer of an interlayer material between the panes, the ratio of the sum of the waviness of both plates (in mm per 300 mm each) to the thickness (in mm) of the intermediate layer is at most 1.0% per mm; the intermediate layer material comprises at least one polymer and has a melting temperature of up to 220°C; and both plates are, independently of each other, glass or glass-ceramic plates; The present invention relates to insulating glass.
[0085] The insulating glass according to the invention is also suitable for use in vertical glazing. The invention also relates for example to doors, windows or walls which comprise insulating glass according to the invention, or to the use of insulating glass according to the invention in doors, windows or walls. [Brief description of the drawings]
[0086] [Figure 1] FIG. 1 shows a measurement setup for determining shear strength. [Diagram 2] FIG. 1 shows force versus displacement curves. [Diagram 3] FIG. 1 shows force versus displacement curves. [Figure 4] 1A to 1C are diagrams illustrating the determination of undulations in a plate 41.
[0087] Figure 1 shows the measurement setup for determining the shear strength. The insulating glass with both panes 4 and 5 and the interlayer 6 is loaded into the lower receiving part 3. The lower receiving part 3 is designed in such a way that the insulating glass is supported up to just before the shear edge (interlayer 6). The upper pressure piece 2 also ends just before the shear edge, so that during shearing the interlayer 6 is exposed. A force 1 is introduced vertically from above and is divided equally into two force components, one perpendicular to the shear plane and one in the shear direction. Shearing therefore takes place under load.
[0088] Figures 2 and 3 show typical force vs. displacement curves. The x-axis shows lateral displacement in mm. The y-axis shows force in N.
[0089] Figure 2 shows typical force-displacement curves for example A. For a lateral displacement of 1-2 mm, a maximum shear force of approximately 1800 N is reached. A noticeable force drop occurs due to the peeling off of the upper glass-ceramic plate from the intermediate layer. A plateau phase for a lateral displacement of 2-6 mm represents the slippage of the glass-ceramic plate along the intermediate layer. From a lateral displacement of approximately 6 mm, a further force drop can be identified, which is due to an increasingly smaller contact area between the glass-ceramic plate and the intermediate layer. At a lateral displacement of approximately 6.5 mm, the force finally drops to 0 N. Complete separation of the upper glass-ceramic plate from the intermediate layer has occurred.
[0090] Figure 3 shows a typical force vs. displacement curve for Example C. For a lateral displacement of about 3 mm, a maximum shear force of about 6500 N is reached. The decrease in force is due to the fracture of the glass ceramic and its increasing instability.
[0091] FIG. 4 shows diagrammatically the determination of the waviness of a plate 41. The waviness of the plate 41 is determined by placing a measuring body 42 with a flat measuring surface and a length of 300 mm on the plate 41 in such a way that the measuring body 42 does not protrude beyond the edge of the plate 41. The measuring body 42 is placed on the plate 41 at two spaced apart points with a distance 44, while due to the waviness of the plate 41, gaps arise between the measuring body 42 and the surface of the plate 41 at other positions. The height 43 of such a gap can be determined, for example, by using a feeler gauge, in particular by arranging the feeler gauge between the surface of the plate 41 and the measuring body 42 and increasing the thickness of the feeler gauge so that the gap between the surface of the plate 41 and the measuring body 42 is just filled at the position of the maximum distance 43 between the surface of the plate 41 and the measuring body 42. The thickness of the feeler gauge then corresponds to the gap height 43. Depending on the position at which the measuring body 42 is placed on the surface of the plate 41, gaps of different heights 43 can arise. The gap with the highest height 43 of all gaps is relevant for the waviness specification. This height 43 is H max It is also called the waviness and is expressed in mm. max The waviness can be expressed as a percentage by abbreviating the unit mm. maxIf is for example 3 mm, then the waviness is obtained as the quotient of 3 mm and 300 mm, and is therefore 1.0%. EXAMPLES
[0092] Insulating glass according to the invention and not according to the invention were investigated with regard to shear strength, mechanical resistance and fire resistance. The ratio of the sum of the waviness (in mm per 300 mm) of both panes to the thickness of the interlayer (in mm) was up to 1.0% per mm, respectively.
[0093] 1. Shear strength The insulating glass investigated consisted of two glass-ceramic panes, each having a thickness of 4 mm, and an interlayer between both panes, made of an interlayer material containing a polymer, the interlayer having a thickness of 0.76 mm. Each insulating glass pane had a length of 20 mm and a width of 10 mm.
[0094] There are differences between the insulating glass regarding the polymer. In the case of example C according to the invention, the polymer was polyurethane. In the cases of examples A and B not according to the invention, the polymer was PVB (polyvinyl butyral) or EVA (ethylene vinyl acetate copolymer). The interlayer material of example C contained a flame retardant material in addition to the polymer.
[0095] The measurement principle is shown in Figure 1. The measurement setup included an upper and a lower holding device, which were loaded with the specimen to be tested. The length of the lower holding device was chosen in such a way that the specimen was supported up to just before the shear edge (laminar layer) (Figure 1). The upper holding device also ended just before the shear edge, so that the laminate was exposed during shearing. The support angle was 45°.
[0096] The force was introduced vertically from above and divided equally into two force components, one perpendicular to the shear plane and the other in the shear direction. Thus, shearing was performed under load. The travel speed was 2 mm / s. The initial load was 10 N. As a test device, a universal tension and compression machine Instron 5969 was used. The measurements were performed at a temperature of 22 °C and a relative humidity of 40% to 60%, especially 50%.
[0097] Insulating glass having the structures according to example A (PVB interlayer), example B (EVA interlayer) and example C (polyurethane interlayer) were tested. The number of samples was 16 samples according to example A, 21 samples according to example B and 39 samples according to example C.
[0098] The PVB interlayer of Example A could be sheared away from the glass ceramic without the glass ceramic fracturing, therefore, there was very little adhesion between the glass ceramic and the PVB interlayer.
[0099] The samples of Example C showed a completely different behavior. The adhesion between the glass ceramic and the polyurethane interlayer was so great that the interlayer could not be sheared off. Thus, in the case of each of the tested samples of Example C, the detachment occurred due to the fracture of the glass ceramic under the shear load. Despite the action of the large shear forces, both glass ceramic plates did not noticeably shift relative to each other.
[0100] In this respect, the shear behavior of Example B was between that of Examples A and C. However, fracture of the glass ceramic occurred in most of the samples. However, the maximum shear force was smaller than in the case of Example C, since the interlayer had already partially delaminate due to the shear load and the upper glass-ceramic plate was significantly displaced. In two samples, the interlayer even delaminates before fracture of the glass ceramic occurs. Thus, the adhesion between the glass ceramic and the EVA interlayer of Example B was better than in the case of Example A, but clearly worse than in Example C.
[0101] The qualitatively different shear behavior of the three examples A-C is reflected in the quantitatively different shear behavior (expressed as maximum shear force per area). As soon as the delamination of the interlayer occurs, a drop in the force occurs. The maximum shear force per area is therefore relatively small (FIG. 2). However, if the interlayer cannot be sheared, as in example C, the shear force increases until finally a fracture of the glass-ceramic plate occurs (FIG. 3). In particular in view of the strong adhesion between the glass-ceramic and the interlayer, the maximum shear force per area is correspondingly high, if the glass-ceramic plates do not even slip relative to each other before the fracture of the glass-ceramic.
[0102] The results are summarized in the table below. Maximum shear force per area is shown as the mean value ± standard deviation.
[0103] [Table 1]
[0104] Example C had by far the best shear strength.
[0105] 2. Pendulum impact test Pendulum impact tests were performed in accordance with the ANSI Z97.1-2015(R2020) standard.
[0106] The insulating glass tested consisted of two glass-ceramic panes, each with a thickness of 3 mm, and an interlayer between both panes, made of the interlayer material according to Example C above, with an interlayer thickness of 0.76 mm. The length of the insulating glass was 1938 mm and the width of the insulating glass was 876 mm.
[0107] Pendulum impact tests were performed according to ANSI Z97.1-2015 (R2020) using specimens with a weight of 45 kg and a drop height of 1220 mm.
[0108] The hole in the insulating glass caused by the impact of the pendulum was less than 76 mm in diameter. The test was therefore passed in accordance with the highest classification of this standard. The insulating glass according to the invention with the interlayer according to example C has excellent mechanical stability.
[0109] 3. Fire resistance Insulating glass having an interlayer according to Example A (PVB plastic) or according to Example C (polyurethane plastic) was tested for its fire resistance.
[0110] a) Example A The insulating glass with the interlayer according to Example A had a length of 2000 mm and a width of 1000 mm. The thickness of the interlayer was 0.76 mm. Both plates were glass-ceramic plates each having a thickness of 4 mm. An interlayer sheet was placed between both plates. A prelaminate was produced from the composite layer thus obtained, from which the insulating glass was obtained by autoclaving.
[0111] The insulating glass was enclosed in a steel frame with a circumferential 15mm glass groove and tested to UL9 in a test oven.
[0112] After 5 minutes, the formation of bubbles in the interlayer was observed. After 6 minutes, destruction of the plate on the fire side occurred. The interlayer, now exposed to the fire, burned forming an intense flame. After 90 minutes, the furnace was switched off. There was still flame retardancy (Raumabschluss). During a hose stream test performed after the furnace was switched off, no further destruction or openings occurred.
[0113] b) Example C The insulating glass with the interlayer according to Example C had a length of 2000 mm and a width of 1000 mm. The thickness of the interlayer was 0.76 mm. Both plates were glass-ceramic plates each having a thickness of 5 mm. An interlayer sheet was placed between both plates. From the composite layer thus obtained, insulating glass was obtained by autoclaving.
[0114] The insulating glass was enclosed in a steel frame with a circumferential 15mm glass groove and tested to UL9 in a test oven.
[0115] After 3 minutes, reaction of the interlayer with bubble formation became visible. After 4 minutes, discoloration of the interlayer occurred. Immediately after bubble formation, the sheet started to flow downwards, thereby causing the bubbles to disappear. No side flame formation was observed. The furnace was switched off after 90 minutes. There was still flame resistance. During the hose stream test performed after the furnace was switched off, no breaks or openings occurred.
[0116] A particular advantage of the insulating glazing with an interlayer according to Example C is therefore its good fire resistance. [Explanation of symbols]
[0117] 1 force 2 Upper pressure piece 3 Lower compartment 4 boards 5 boards 6. Middle Tier 41 board 42 Measurement object 43 Height 44 interval
Claims
1. 1. An insulating glass comprising at least two sheets and an interlayer of an interlayer material between the sheets, the ratio of the sum of the waviness of both plates (each in mm per 300 mm) to the thickness (mm) of the intermediate layer is at most 1.0% per mm; the intermediate layer material comprises at least one polymer and has a melting temperature of up to 220°C; and both said plates, independently of each other, are glass or glass-ceramic plates; The double glazing.
2. 2. The insulating glass according to claim 1, wherein each of the two panes has a thickness in the range of 2.0 to 15.0 mm, the interlayer has a thickness in the range of 0.3 to 5.0 mm, and / or the insulating glass has a thickness in the range of 5.0 to 15.0 mm.
3. 3. The insulating glass according to claim 1, wherein at least one of the two panes is a borosilicate glass pane or a glass-ceramic pane.
4. 4. The insulating glass according to claim 1, wherein the polymer is a polyurethane.
5. 5. The insulating glass according to claim 1, wherein the interlayer material comprises, in addition to plastic, a flame retardant material.
6. 50% by weight of the mass loss of the intermediate layer material in thermogravimetry (TGA) according to DIN EN ISO 11358-1:2014-10 occurs at a temperature of less than 425°C; in power-compensated differential scanning calorimetry (DSC) according to DIN EN ISO 11357-1:2017-02, a sample of the intermediate layer material and a reference vessel are placed in a thermally isolated oven, which is controlled in such a way that the same temperature always prevails on both sides, and a power requirement for this is less than 0.60 mW on average per mg of intermediate layer material in the temperature range from 100° C. to 200° C.; and / or the intermediate layer material has a residue on ignition according to DIN EN ISO 3451-1:2019-05 of at least 0.20% by weight at a temperature of 625 ° C; The insulating glass according to any one of claims 1 to 5.
7. 7. The insulating glass according to claim 1 , wherein the insulating glass has a flame protection property according to UL9, 8th edition, March 2020, or according to UL10, in particular according to UL10B, 10th edition, February 2008, or according to UL10C, 3rd edition, June 2016, after 90 minutes.
8. Maximum shear force per area is at least 17.5 N / mm 2 The insulating glass according to any one of claims 1 to 7,
9. 9. The insulating glass according to claim 1 , wherein at least one of the two panes has an acid resistance class 2 according to DIN 12116: 2001-03, an alkali resistance class A1 according to DIN ISO 695: 1994-02 and / or a hydrolysis resistance class HGB1 according to ISO 719: 2020-09.
10. A method for producing insulating glazing, in particular insulating glazing according to any one of claims 1 to 9, comprising the following steps: providing two plates, which are independent of each other and are glass or glass-ceramic plates; - providing an intermediate layer sheet; - placing said sheet between both plates to obtain a composite layer; and - Autoclave treatment to obtain insulating glass The method comprising:
Citation Information
Patent Citations
Integrated glass structure, method for its manufacture and application
EP2199075A1
Helical scanning type tape recorder
JP1983023338A
Instrument for measuring configuration of surface of plate glass
JP1991235012A
Borosilicate glass and utilization of the same
JP2004083403A
Laminated glass and its manufacturing method
JP2005001953A
